A geological case for movement between Canada and Greenland along Nares Strait - H. Newman, Patricia (Meddelelser om Grønland. Geoscience, 1982)
Nares Strait, part of a 1400 km long lineament between Canada and Greenland, may be one arm (along with Lancaster Sound and Baffin Bay) of a triple junction. Study of the geological literature on the area from northern Baffin Island to northern Greenland revealed a number of possibly important markers and structural features. The most important of these are: 1) the structural boundary between deformed and undeformed rocks at the margin of the Palaeozoic fold belt of northern Ellesmere Island and Greenland and 2) the large asymmetrical northwest-trending graben systems of northern Baffin Island and Greenland, whose fault blocks tilt to the northeast and southwest respectively. Correlation of these features across Nares Strait suggests that movement along the Strait of a minimum of 200 km has occurred since the mid-Palaeozoic, and a maximum of 300 km since late Precambrian times. It seems probable that the movement occurred in a number of episodes, beginning with rifting in the Proterozoic and ending in the Tertiary Eurekan orogeny.